Report on hearing loss in oncology - Schultz,Christiane (2009)
Cisplatin is used frequently as an antineoplastic drug in the treatment of many different cancers. However, when used in doses over 360mg/m², ototoxicity may ensue, resulting in loss of hearing. Criteria for identifying and quantifying hearing loss have been devised. AIM: To describe the features of different hearing loss classification systems and to identify their implications and use in oncologic patients. METHOD: Hearing loss was classified in 31 patients before and after chemotherapy, according to different criteria, assessing the sensitivity and specificity of each classification system. RESULTS: Hearing loss results were highly variable (ranging from 29% to 61%). Only 4 of 31 subjects with post-therapy hearing loss were identified by all the methods. A few subjects with hearing loss were classified as normal hearing in some of the criteria. A normal PTA was found in 18 of 31 subjects in the post-treatment evaluation. CONCLUSION: None of the criteria assesses the complaints of patients. The criteria described in this study were inadequate to identify hearing loss following chemotherapy, requiring additional information for physicians to better understand the hearing losses and their implications for the quality of life of patients.